Pembelajaran IPS dalam Perspektif Global - Supriyanto, Supriyanto; Isbandiyah, Isbandiyah (LP4MK STKIP PGRI Lubuklinggau, 2025)
Abstract This article is the result of a review of various literatures, with the aim of describing the social studies learning process in a global perspective. The results of this study can be described as that the global perspective emphasizes every human being as a citizen of the world. So that social interaction is also not only with close community members but also with citizens of the world. Therefore, teachers must instill good values in students and provide an understanding that their lives and ours are part of the life of the world. The role of teachers in instilling good values is as a communicator or liaison between students and the outside world. For this reason, a teacher must care about events and activities in the community, both in the local, national, and international communities; actively seeking information related to lessons nationally and internationally; teachers must be open and receptive to reforms; and able to select information according to needs. In addition, social studies learning in a global perspective invites students to think globally and act locally by prioritizing the principle of conservation over locality. Global issues and problems are studied from a global perspective and implemented in social studies learning. Global issues that can be discussed in social studies learning are population and family planning, development, human rights, migration, global common ownership, environment and natural resources, hunger and foodstuffs, peace and security, prejudice and discrimination.